If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 9 = 2g + -5 Reorder the terms: 9 = -5 + 2g Solving 9 = -5 + 2g Solving for variable 'g'. Move all terms containing g to the left, all other terms to the right. Add '-2g' to each side of the equation. 9 + -2g = -5 + 2g + -2g Combine like terms: 2g + -2g = 0 9 + -2g = -5 + 0 9 + -2g = -5 Add '-9' to each side of the equation. 9 + -9 + -2g = -5 + -9 Combine like terms: 9 + -9 = 0 0 + -2g = -5 + -9 -2g = -5 + -9 Combine like terms: -5 + -9 = -14 -2g = -14 Divide each side by '-2'. g = 7 Simplifying g = 7
| 7(2y+6)=4y+72 | | (2x-3)=(3x-5) | | 10x^6+8x^4=0 | | x=27+-2x | | x-10/x+2=7 | | -2.7=-1.3+0.7x | | x-(8x^(1/2))+4=0 | | 8/11(n+10)=64 | | -3x+12=9 | | 9-y=9 | | 15x-45+3x=18x+18-13 | | x+0.07x=16.05 | | 9x-1=8x+19 | | (9x+2)/5=4 | | (3x^2+2x-9)-(-3x+4)= | | -3-y=9 | | (3y/2a)/(8a^2y5/15y) | | 6x^2+2x-58=0 | | 2.3x-9.34=6.3 | | 4/17(x)=20 | | 3x-14=2x+19 | | -40-3x=14-10x | | 3-2(1/7) | | 8c+c=27 | | -4y-2+3y+4=-5 | | 24w^9x^6y-22x^4y^6= | | 2(1/7) | | 1x-6=3x-4 | | -[4(7)+2]-[3(7)-4]=x | | 4b+29=48 | | -[4(7)+2]-[3(7)-4]=-5 | | 3-21/7 |